Barrett, Arthur. Interview about his career in Newfoundland radio and television broadcasting. - Swain, Hector K. (1990)
Arthur Barrett talks about his career in Newfoundland radio and television broadcasting. Barrett was involved with the Canadian Armed Forces radio, VOWN in Corner Brook, VORG in Gander, the USAF radio and CFSN TV in Stephenville. 00:00 - Hector Swain outlines what he would like to talk about; 01:37 - Arthur Barrett talks about being stationed in England with the RCAF, then sent to Germany where he was involved with the Canadian Armed Forces radio; 1946 became a radio announcer with VOWN in Corner Brook, then promoted and transferred to Gander as a manager of the Gander station; In gander 1948 to 1956 and transferred to USAF in Stephenville as CBC management representative and the staff were American servicemen. He was there till 1964; 04:18 - Transferred to Corner Brook as the manager of television operations in Corner Brook until 1972; 04:35 - Moved to St. Johns as coordinator of program planning then Regional manager of services and remained in that position to 1983; 05:20 - Stephenville was CFSN TV, American oriented but Newfoundland licenced; Carried a American religious program; 06:50 - In radio in Corner Brook they carried Morning Devotions; 07:10 - The radio station in Stephenville was also an american armed forces radio; 07:55 - Talks about Gander radio schedule; 08:50 - Morning Devotions from St. John’s and creating their own program but it was not successful; 10:17 - Talking about Invitation to Worship program [recording interrupted by Mrs. Barbara Barrett offering Tea], Barrett felt he was a token Protestant; Hiram Silks program; 15:37 - Humanitarian broadcasting and the Gerald S. Doyle Bulletin; 17:40 - Woodland Echoes in Corner Brook; 19:22 - Talks about Aubrey Mac [MacDonald] 21:47 - Talk about Bob MacLeod and the Newfoundland Savings program; 24:33 - Talks about C.J Penney; 27:15 - [The Yarns of] Sandy Joe with Mike Gillis; 29:45 - The Salvation Army broadcasts; 30:45 - This is London Calling with Margot Davies; 32:00 - The philosophy of CBC and the radio media; 36:00 - Tells story about being ...